Gendered debt – a scoping study review of research on debt acquisition and management in single and couple households. Issue 5 (2nd September 2020) - Callegari, Julia; Liedgren, Pernilla; Kullberg, Christian
ABSTRACT: In the current economic environment, social workers are increasingly being required to support households that suffer from severe debt burdens. However, previous research has questioned if social workers are sufficiently prepared to meet this emerging form of financial exclusion, especially from a gender perspective. Thus, there is a risk that interventions for indebted households will overlook gender-specific, inequality-generating patterns in the acquisition and management of debts. With this in mind, the aim of this article is to provide an overview of the existing literature related to gender and household debt, in order to enable a development towards gender-aware social work interventions that equally support women and men in creating financially stable lives. The results show that gender dynamics affect how households acquire and manage their debt. These dynamics result in different forms and levels of debt for women and men, unequally divided spheres of responsibility for managing the acquired debt burden and differences in their willingness to seek debt advice. Unequal power relations between men and women and gender-stereotypic expectations are found to be key factors for explaining these results. The results are discussed in relation to practical implications for social policy and social work practice.